The Influence of Wet Granulation Parameters on the Compaction Behavior and Tablet Strength of a Hydralazine Powder Mixture - Oliver Macho; Ľudmila Gabrišová; Adam Guštafík; Kristian Jezso; Martin Juriga; Juraj Kabát; Jaroslav Blaško (MDPI AG, 2023)
The aim of this paper was to describe the influence of high-shear wet granulation process parameters on tablet tensile strength and compaction behavior of a powder mixture and granules containing hydralazine. The hydralazine powder mixture and eight types of granules were compacted into tablets and evaluated using the Heckel, Kawakita and Adams analyses. The granules were created using two types of granulation liquid (distilled water and aqueous solution of polyvinylpyrrolidone), at different impeller speeds (500 and 700 rpm) and with different wet massing times (without wet massing and for 2 min). Granulation resulted in improved compressibility, reduced dustiness and narrower particle-size distribution. A significant influence of wet massing time on parameters from the Kawakita and Adams analysis was found. Wet massing time had an equally significant effect on tablet tensile strength, regardless of the granulation liquid used. Granules formed with the same wet massing time showed the same trends in tabletability graphs. Tablets created using a single-tablet press (batch compaction) and an eccentric tablet press showed opposite values of tensile strength. Tablets from granules with a higher bulk density showed lower strength during batch compaction and, conversely, higher strength during eccentric tableting.